Development of an integrated core–edge scenario using the super H-mode. (22nd November 2021) - Wilks, T.M.; Knolker, M.; Snyder, P.B.; Eldon, D.; Scotti, F.; Chrystal, C.; Laggner, F.M.; Lasnier, C.; Mclean, A.; Osborne, T.; Paz-Soldan, C.; Wang, H.; et al.
Abstract: An optimized pedestal regime called the super-H (SH) mode is leveraged to couple a fusion relevant core plasma with a high density scrape-off layer appropriate for realistic reactor power exhaust solutions. Recent DIII-D experiments have expanded the operating space of the SH regime using advanced control algorithms and investigated optimization of impurity seeding, deuterium gas puffing, and 3D magnetic perturbations. Simultaneous real-time control of the pedestal density and radiated power with in-vessel coils and nitrogen seeding enable optimal coupled divertor and pedestal conditions. Four case studies are analysed with varied levels of radiated power in the divertor volume ranging from 0 (no seeding) to 8.5 MW radiated from carbon and nitrogen emission. Plasmas with a 4.5 MW radiated power target establish a radiative mantle, leading to divertor temperatures of ∼16 eV while maintaining SH-mode, and with only marginal impact on the pedestal and core performance. Increased levels of N2 seeding with a 7.5 MW radiated power target facilitate detachment onset and divertor temperatures <5 eV, with no degradation in stored energy and the operational point remaining inside the SH-mode channel for > 2.5 τ E . Finally, a 8.5 MW radiated power target leads to partial detachment, which is so far associated with the loss of access to SH-mode pedestal conditions.